Geiger mode theoretical study of a wafer-bonded Ge on Si single-photon avalanche photodiode. (10th January 2017) - Ke, Shaoying; Lin, Shaoming; Huang, Wei; Wang, Jianyuan; cheng, Buwen; Liang, Kun; Li, Cheng; Chen, Songyan
Abstract: The investigation of the single-photon properties of a wafer-bonded Ge/Si single-photon avalanche photodiode (SPAD) is theoretically conducted. We focus on the effect of the natural GeO2 layer (hydrophilic reaction) at the Ge/Si wafer-bonded interface on dark count characteristics and single-photon response. It is found that the wafer-bonded Ge/Si SPAD exhibits very low dark current at 250 K due to the absence of threading dislocation (TD) in the Ge layer. Owing to the increase of the unit-gain bias applied on the SPAD, the primary dark current ( I DM ) increases with the increase in GeO2 thickness. Furthermore, the dependence of the linear-mode gain and 3 dB bandwidth (BW) for the dark count on GeO2 thickness is also presented. It is observed that the dark count probability of the Ge/Si SPAD significantly increases with the increase in GeO2 thickness due to the increase of the I DM and the reduction of the 3 dB BW. It is also found that with the increase in GeO2 thickness, the external quantum efficiency, which affects the single-photon detection efficiency (SPDE), drastically decreases because of the blocking effect of the GeO2 layer and the serious recombination at the wafer-bonded Ge/Si interface. The afterpulsing probability (AP) shows an abnormal behavior with GeO2 thickness. This results from the decrease in avalanche charge and increase in effective transit time.